Produção de forragem e atividade microbiana do solo em sistemas silvipastoris com capim-buffel como componente forrageiro - Matheus Almeida Alves (2021)
The use of integrated production systems aims to diversify the production of agricultural areas, allowing the use of multiple species arrangements in a sustainable production model. The management of forage species in monoculture is consolidated in Brazil, however production in integrated systems requires studies to understand the soil-plant interactions in the implantation and development of forages. Thus, this study aimed to evaluate the microbial biomass and soil enzymatic activity, the productivity of buffel grass (Cenchrus ciliares cv. Aridus) intercropped with eucalyptus (E. urophylla x E. grandis) (SP1) and intercropped with black beans pigeon pea (Cajanus cajan cv. Iapar 43) and eucalyptus (SP2) in silvopastoral systems, using a 3 x 20 m arrangement. The experimental design used was in randomized blocks with four replications, in a 2 x 4 factorial arrangement, where the first factor is related to crops intercropped with eucalyptus (grass-buffel and grass-buffel + pigeon pea), and the second factor refers to allocation of assessment points from the eucalyptus tree lines (2m, 4m, 6m, 8m). Plant evaluations started simultaneously with soil evaluations 150 days after planting, following thinning of pigeonpea plants. The collection of plants was performed to determine green mass, dry mass, morphological composition (%) of leaf, stem and senescent material. At the time of thinning, the height of the canopy and the root mass were also measured. Soil collection was carried out at depths 0-5, 5-10 and 10-20 cm to determine microbial nitrogen (Nmic) and carbon (Cmic). Collections at depths of 0-5 and 5-10 cm were performed to evaluate the activity of β-glycosidase and urease enzymes. The data obtained were submitted to the Tukey test (p <0.05) with the aid of software R, version 4.0.3. In the distances of 6 and 8 meters from the eucalyptus, the values of canopy height (CD) and root mass (RM) of the buffel grass were higher in the SP1 system compared to SP2. The increase in the distances of the eucalyptus lines contributed to the decrease in the percentage of leaves and an increase in the percentage of stalk, while the dry mass did not differ between treatments. The dry matter (DM) showed the highest percentage in the distance of 8m in SP1 and 6m in SP2. In relation to Cmic, there was no interaction, and only at a depth of 5-10 cm was there a difference where the value was greater at a distance of 2 m from the eucalyptus. For Nmic, the values decreased as it moved away from the eucalyptus line at a depth of 5-10 cm. The activity of the β-glycosidase enzyme was greater at a distance of 2 m in the SP1 system for the two depths evaluated. In the SP2 system, the lowest value was found in the distance of 2m for the depth 0-5 cm. The activity of the urease enzyme was less than 8 m away from the eucalyptus for the two depths evaluated. Given the above, it is concluded that the productivity of the buffelgrass was higher in the SP1 system, while the microbiological attributes of the soil had a better response in the SP2 system, as pigeonpea and eucalyptus inhibited the growth and productivity of the buffelgrass.